Associations Between Chronotype and Salivary Endocrinological Stress Markers. (April 2013) - Toda, Masahiro; Kawai, Tomoko; Takeo, Keiko; Rokutan, Kazuhito; Morimoto, Kanehisa
<x xml:space="preserve">Abstract</x> Objectives. To investigate the effect of chronotype on salivary cortisol or salivary α-amylase (sAA). Methods. From 108 male university students, saliva samples were collected in the afternoon (between 15:00 and 17:00). The salivary cortisol and sAA levels were determined with commercial kits. Chronotype was quantitatively evaluated using the Horne and Östberg Morningness–Eveningness Questionnaire. Subjects were categorized into morning types and evening types. Results. The sAA levels were lower in the morning types than in the evening types. We found no significant difference in salivary cortisol levels between the two groups. Conclusions. These findings suggest that the sAA levels may be associated with chronotype.